THE CORRELATION BETWEEN STUDENTSâ€™ LEARNING INTEREST AND STUDENTSâ€™ ENGLISH READING ACHIEVEMENT AT THE SECOND SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF BINA SARANA INFORMATIKA UNIVERSITY - Rahayuningsih, Retno; Rosalinah, Yanti; Subroto, Ibnu (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2022)
Reading is an activity for setting information and meaning of the text in the language. There is another aspect that has correlation to reading achievement, one of them is interest of students. Interest is a prefer feeling and interested in something or activity without any instructions from other people. This research was aimed at finding out there was a correlation between the studentsâ€™ learning interest and studentsâ€™ reading achievement. This research was quantitative research design. The writer used test method to get data about reading achievement of the students, questionnaire method to get data about the studentsâ€™ interest in learning English. The test method data is processed by product moment correlation.This research was conducted at the second semester students of English study program of Bina Sarana Informatika University. The subject of this research was consisting 32 students. Moreover, The result of data analysis; â€œrobservedâ€ = 0.541, rtable = 0.361 or 0.463. After considering the product moment table by using df 30, the critical value of product moment (rtable) 5% level is 0.361, rtable for 1% level is 0.463 it means that it can be inferred that the Alternative Hypothesis (Ha) is accepted. There is a positive and significant correlation between the studentsâ€™ learning interest and studentsâ€™ reading achievement at the second semester students of English Study Program of Bina Sarana Informatika University.